Rovesci culturali paradossali, tra Cordero e San Paolo - Heritier, Paolo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
The article begins with the case of Cordero’s expulsion from the Catholic University, and his diatribe with Cardinal Colombo. The paper analyzes the fundamentally Nietzschean reading of Pauline anthropology and proposed liberation of juridical rationality from religious irrationality within Cordero’s Letter to Romans commentary. To critical argumentation the article opposes the renew of twentieth-century Christology, which is considered capable of going beyond Cordero’s criticism, while at the same time providing intelligibility of his historical perspective: hoping of being able to rearticulate on a different basis the relationship between legal and anthropological thought of the West in crisis, and the renewed contemporary vision of Christian theology.